2014
DOI: 10.1159/000370051
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Pattern and Risk of Chronic Kidney Disease: The Kansai Healthcare Study

Abstract: Background/Aims: The association between alcohol consumption and the risk of chronic kidney disease (CKD) has been reported. What is not known is whether drinking pattern combined with the weekly frequency of alcohol consumption and the quantity per drinking day is associated with the risk of CKD. Methods: We enrolled 9,112 Japanese nondiabetic men aged 40 to 55 years with absence of proteinuria, an estimated glomerular filtration rate (eGFR) of 60 ml/min/1.73 m2 or higher, and not on antihypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 24 publications
0
38
1
Order By: Relevance
“…24 We found that subjects who had an alcohol consumption of 23.1–46.0 or 46.1–69.0 g ethanol/drinking day on 4–7 days per week showed a significantly lower risk of developing CKD compared with non-drinkers. However, alcohol consumption of ≥69.1 g ethanol/drinking day was not associated with risk of CKD, regardless of the number of drinking days per week.…”
Section: Discussionmentioning
confidence: 71%
“…24 We found that subjects who had an alcohol consumption of 23.1–46.0 or 46.1–69.0 g ethanol/drinking day on 4–7 days per week showed a significantly lower risk of developing CKD compared with non-drinkers. However, alcohol consumption of ≥69.1 g ethanol/drinking day was not associated with risk of CKD, regardless of the number of drinking days per week.…”
Section: Discussionmentioning
confidence: 71%
“…33 On the other hand, alcohol consumption has been inversely associated with the risk of CKD. [25][26][27][35][36][37] A prospective cohort study of 11 023 initially healthy male physicians in the United States reported a significantly lower risk of renal dysfunction (defined as serum creatinine ⩾ 1.5 mg/dl and eGFR ⩽ 55 ml/min) in those who consumed at least 7 drinks weekly. 37 A prospective cohort study in China reported a significant inverse relationship between alcohol consumption and risk of ESRD in men and a stronger relationship in those who had more than 21 drinks weekly.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several previous epidemiological studies have showed that moderate alcohol consumption was associated with a decreased risk of CKD [17][18][19]29], although the serum uric acid levels increase with increasing alcohol consumption [6][7][8][9][10]. Therefore, an adjustment for alcohol consumption is necessary for a more accurate assessment of the effect of serum uric acid level on the incident CKD.…”
Section: Discussionmentioning
confidence: 91%